"Cell and tissue, shell and bone, leaf and flower" – On Growth and Form in Context. (June 2017) - Jarron, Matthew
Abstract: D'Arcy Thompson wrote his most celebrated book, On Growth and Form, at University College, Dundee in the 1910s. This paper explores some of the influences on Thompson's ideas and the context in which the book was written. It examines the controversial nature of some of the book's content and the connections between science and art that it embodies. The book's reception is discussed and the gradual take-up of his ideas within biology, as well as looking at the many other fields that have been influenced by Thompson's ideas.